A Nigerian perspective of continuing education and knowledge economy (2024)
Adult education programmes in both developed and developing nations usually include continuing education. The relationship between the two notions is that someone requires additional information, either inside or outside of school systems, in order to remain relevant wherever one is at any given time. The information, communication, and technology era brought in a knowledge economy that should normally support continuing education, nevertheless there are still obstructions that prevent people from learning. Although these hurdles are both personal and structural, there seems be no justification for anyone to remain without information for the purpose of individual and group survival. Continuing education and knowledge economy are two concepts that have become popular in educational theory and practice but they are not combined as related concepts in literature. This is an attempt to clarify the concepts for both professional and practicing adult educators generally in African countries and particularly in Nigeria where policy documents for the practice of adult education sometimes deviate from the extant principles and theories. This paper used a conceptual analysis of terms and a systematic review of the available literature. It concludes that continuing education and the knowledge economy necessitate more access to learning that takes into account individual needs and requirements from organisations. This is as a result of the increased availability and application of knowledge in positively changing human conditions.